Briefing: Comments on the masonry ceiling at St George's Hall, Liverpool, UK. Issue Volume 172:Issue EH 1(2019:Feb.) (7th January 2019) - Ray, Stephen F
Abstract : St George's Hall, Liverpool, UK, is about 170 years old and is described as an outstanding building. During construction, however, doubts were expressed about its structural integrity, particularly relating to the masonry arch. The 20 m wide arch is constructed from tube-like bricks placed as headers only one brick thick at the crown. Making the bricks hollow reduced the weight of the arch and allowed air to flow from the hall into the roof space as part of the air-conditioning system. In none of the references quoted was a description found of the basis of the design or proofs to demonstrate that the arch was stable. Rawlinson, the civil engineer, privately published correspondence between himself and Elmes, the architect, to show their belief in the building construction. A crude assessment indicates possible admissible load paths. Further searches and investigation would provide a more informative statement on the structural integrity of the arch.